Species richness, but not phylogenetic diversity, influences community biomass production and temporal stability in a re-examination of 16 grassland biodiversity studies - Venail, Patrick (2015)
Hundreds of experiments have now manipulated species richness of various groups of organisms and examined how this aspect of biological diversity influences ecosystem functioning. Ecologists have recently expanded this field to look at whether genetic diversity among species, often quantified as the degree of evolutionary divergence on a molecular phylogeny, also predicts ecological function. Some have hypothesized that phylogenetic divergence should be a superior predictor of ecological function than species richness because evolutionary relatedness represents the degree of ecological and functional differentiation among species. But studies to date have provided mixed support for this hypothesis. Here, we re-analyze data from 16 experiments that have manipulated plant species richness in grassland ecosystems and examined the impact on aboveground biomass production over multiple time points. Using a new molecular phylogeny of the plant species used in these experiments, we quantified how the phylogenetic diversity of plants impacts average community biomass production as well as the stability of community biomass production through time. Using four complementary analyses we show that, after statistically controlling for variation in species richness, phylogenetic diversity (the sum of branches in a molecular phylogenetic tree connecting all species in a community) is neither related to mean community biomass nor to the temporal stability of biomass. These results run counter to past claims. After controlling for species richness, phylogenetic diversity was positively related to variation in community biomass over time via an increase in individual species variances but this relationship was not strong enough to influence community stability. In contrast to the non-significant relationships between phylogenetic diversity, biomass, and stability, after controlling for species richness, our analyses show that species richness tends to increase the mean biomass production of plant communities, after controlling for phylogenetic diversity. The relationship between species richness and temporal variation in community biomass was either non-significant or negative depending on which analysis was used. However, the increases in community biomass with species richness, independent of phylogenetic diversity, always led to increased stability. These results suggest that phylogenetic diversity is no better as a predictor of ecosystem functioning than species richness. Synthesis. Our study on grasslands offers a cautionary tale when trying to relate phylogenetic diversity to ecosystem functioning as there may be trait and functional variation among species that cannot be explained by their evolutionary relatedness. Management recommendations suggesting the conservation of evolutionarily distinct species will lead to more productive and more stable communities under changing environmental conditions are not well supported by the data explored in this study.